Optimizing Administrative Services through Interpersonal Communication: Strategies of the Head of Administration at a Madrasah Aliyah in Palembang - Khairunnisa, Aisyah; Afriantoni, Afriantoni; Badaruddin, Kms; Annur, Saipul (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to analyze the interpersonal communication strategy of the Head of Administration at MAN 2 Palembang in the context of management administration services. The type of research carried out is field research and uses a qualitative approach through observation, interviews and documentation. Using a purposive sampling technique, the informants in this research were the head of administration (KTU), school principals, teachers and staff. Data analysis techniques use data reduction, data presentation, and drawing conclusions. This research found that the head of administration at MAN 2 Palembang had implemented three strategies, namely first, a formalist structural strategy by prioritizing manners, proportion and professional service with the principles of kinship and mutual respect. Second, a humanist cultural strategy by creating an atmosphere that is supportive, together and full of empathy. And third, an inclusive equality strategy by creating a supportive, fair and open environment. Thus, the interpersonal communication of the head of administration at MAN 2 Palembang was successful because it integrated credibility, integrity and clear message delivery by implementing these three strategies.